2016
DOI: 10.1063/1.4954678
|View full text |Cite
|
Sign up to set email alerts
|

Lattice thermal conduction in ultra-thin nanocomposites

Abstract: We have studied the lattice thermal conductivity of Si/Ge periodic nanocomposites (superlattice, nanowire, and nanodot structures) of sample sizes in the range of 30 nm–30 μm, periodicities 1.1 nm and 2.2 nm, with reasonably dirty interfaces, and n-type doping concentration in the range of 1023–1026 m−3. Our calculations employ a judicious combination of ab initio and physically sound semi-empirical methods for detailed calculations of estimates of phonon scattering rates due to anharmonicity and interface for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Molecular dynamics simulations by Landry et al [19] and the ab initio work by Garg and Chen [20] using the single-mode relaxation time approximation of the Boltzmann transport equation clearly show that the crossplane κ in SiGe SLs of thin periodicities fall below the alloy limit. A semi-empirical study [21] also confirmed that these systems exhibit promise, however it relies on the tuning of scattering parameters against experimental results. It therefore lacks a degree of predictive power.…”
Section: Introductionmentioning
confidence: 88%
“…Molecular dynamics simulations by Landry et al [19] and the ab initio work by Garg and Chen [20] using the single-mode relaxation time approximation of the Boltzmann transport equation clearly show that the crossplane κ in SiGe SLs of thin periodicities fall below the alloy limit. A semi-empirical study [21] also confirmed that these systems exhibit promise, however it relies on the tuning of scattering parameters against experimental results. It therefore lacks a degree of predictive power.…”
Section: Introductionmentioning
confidence: 88%
“…Hijazi and Kazan [5] presented a predictive Boltzmann model for the cross-plane thermal conductivity in superlattices. Si-Ge superlattices doped by SiGe and Ge nanodots were also studied theoretically, and the results manifested the contributions of nanodots to limiting the thermal conductivities [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%